Calculation of the Time Interval of Radio Storm Emitted from Jupiter - M. Abood, Kamal; H. Ibrahim, Rasha; F. Kahadom, Zeina (Iraqi Journal of Science, 2023)
A program in Visual Basic language was designed to calculate the time interval of radio storm by predict their type at specific Local Time (LT) from Baghdad location, such storms result from the Central Meridian Longitude (CML) of system ΙΙΙ for Jupiter and phase of Io’s satellite (ФIo). These storms are related to position of Io (Io- A,B,C,D). The input parameters for this program were the observer’s location (longitude), year, month and day. The output program results in form of tables provide the observer information about the date and the LT of beginning and end of each type of emitted storm. The year 2011 was taken to apply the results within twelve month; the results of the time interval of radio storm were between (0.08h-5.41h) hours. The obtained results reveal a good agreement as compared with the results of (Radio Jove) software.